Concentrating on the fall of the labor share - Autor, David H.; Dorn, David; Katz, Lawrence F.; Patterson, Christina; van Reenen, John (London, 2017)
"In this paper, we discuss an explanation for the fall in share of labour in GDP based on the rise of “superstar firms.” If globalization or technological changes advantage the most productive firms in each industry, product market concentration will rise as industries become increasingly dominated by superstar firms with high profit margins and a low share of labor in firm value-added and sales. As the importance of superstar firms increases, the aggregate labour share will fall. This hypothesis suggests that sales will increasingly concentrate in a small number of firms and that industries where concentration rises most will have the largest declines in the labour share. We find support for these predictions aggregating up micro-data from the US Census 1982-2012."